2019
DOI: 10.1016/j.clnesp.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of factors associated with energy expenditure in the critically ill

Abstract: Background and aims: Indirect calorimetry is the reference standard for energy expenditure measurement. Predictive formulae that replace it are inaccurate. Our aim was to review the patient and clinical factors associated with energy expenditure in critically ill patients. Methods: We conducted a systematic review of the literature. Eligible studies were those reporting an evaluation of factors and energy expenditure. Energy expenditure and factor associations with p-values were extracted from each study, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 129 publications
(88 reference statements)
3
31
0
1
Order By: Relevance
“…One study on healthy volunteers did not find a significant difference in resting metabolic rate between men and women when adjusted for lean body mass, and fat mass explained a significant variation of resting metabolic rate in women [28]. A recent systematic review discussed several patient and clinical factors that influence EE [29]. This issue may explain the inconsistencies and contradictions regarding published results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study on healthy volunteers did not find a significant difference in resting metabolic rate between men and women when adjusted for lean body mass, and fat mass explained a significant variation of resting metabolic rate in women [28]. A recent systematic review discussed several patient and clinical factors that influence EE [29]. This issue may explain the inconsistencies and contradictions regarding published results.…”
Section: Discussionmentioning
confidence: 99%
“…The American Society of Parenteral and Enteral Nutrition guideline also favors the use of IC to determine EE. In the absence of IC, this guideline suggests to use either a predictive equation or a simplistic weight-based equation (25)(26)(27)(28)(29)(30) kcal/kg/day) [6]. Since a calorimeter and trained personnel are not widely available, various prediction equations for calculation of EE have been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that REE is influenced by many factors, including age, sex, body composition, body temperature, body movement, environmental temperature, heart rate, and disease status [ 26 28 ]. Pharmacological agents, such as analgesics, sedatives, and muscle relaxant reduce REE, while vasopressors increase REE [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Predictive equations estimate a patient's energy expenditure using anthropometry and vital parameters to estimate EE. All equations are unreliable, as EE is affected by many individual factors unaccounted for in the formulas [1,7,19,31,55,[91][92][93][94][95]. When comparing the results of predictive equations to those of IC, many discrepancies are found [18].…”
Section: Predictive Equations To Estimate Energy Expenditurementioning
confidence: 99%